Influence of mode of delivery on satisfaction with hospitalization for childbirth in the study Birth in Brazil - Dayana Dourado de Oliveira Costa; Valdinar Sousa Ribeiro; Marizélia Rodrigues Costa Ribeiro; Ana Paula Esteves-Pereira; Maria do Carmo Leal; Antônio Augusto Moura da Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Controversial results have been reported on the association between mode of delivery and patient satisfaction. This study investigates which mode of delivery leads to greater satisfaction with hospital admission for childbirth. A cohort study was conducted with data from the Birth in Brazil study, which began in 2011. A total of 23,046 postpartum women were included from a random sample of hospitals, selected by conglomerates with a three level stratification. At the first follow-up, 15,582 women were re-interviewed. Mode of delivery, dichotomized into vaginal or cesarean section, and confounders were collected before hospital discharge. The outcome maternal satisfaction, investigated as a 10-item unidimensional construct, was measured by the Hospital Birth Satisfaction Scale up to six months after discharge. We used a directed acyclic graph to define minimal adjustment variables for confounding. The effect of mode of delivery on satisfaction was estimated using a structural equation model with weighting by the inverse of the probability of selection, considering the complex sampling design. The weight was estimated considering the different sample selection probabilities, the losses to follow-up, and the propensity score, which was estimated in a logistic regression model. The analysis revealed no significant difference in satisfaction with hospitalization for childbirth between respondents who had vaginal delivery and cesarean section in the adjusted analysis (standardized coefficient = 0.089; p-value = 0.056). Therefore, women who had vaginal delivery and cesarean section were equally satisfied with their hospitalization for childbirth.